Lateral Epicondylar Fissure Fractures after Transcondylar Screw Placement for the Treatment of Humeral Intracondylar Fissures and Humeral Condylar Fractures - Piana, Francesco; Wylie, Sebastian; Belch, Alex; Barthelemy, Nicolas; Carwardine, Darren; Ogden, Dan; Parsons, Kevin (Veterinary and Comparative Orthopaedics and Traumatology, 2025)
The aim of this study was to report an intraoperative complication that has been noted during the surgical application of transcondylar screws (TCS). Although a recent study has shown medial epicondylar fissure fractures during medial to lateral TCS application in dogs treated for humeral intracondylar fissures (HIF), our study pertains to lateral epicondylar fissure fractures occurring during surgery for HIF, lateral condylar fractures and intracondylar Y fractures.Retrospective, multicentre case series, including seven client-owned dogs. Data collection included signalment, imaging findings, surgical method and implants used for the repair, postoperative complications and outcome at 6 to 8 weeks of follow-up.Two dogs were treated for bilateral HIF, one for unilateral HIF, two for lateral condylar fractures and two for intracondylar Y fractures. Intervention after diagnosing the intraoperative lateral fissure fracture included adding a washer and a transcondylar Kirschner wire or an adjunctive TCS. One dog was euthanatized due to financial constraints following implant failure 2 weeks after lateral condylar fracture repair. Six dogs had a good outcome with return to function.Humeral epicondylar fissure fractures can occur in the lateral epicondyle during TCS placement in dogs treated for HIF, lateral condylar fractures and intracondylar Y fractures.
Keywords: dogs; elbow; fracture fixation; orthopaedic surgery; intraoperative complications